Prevention of Postoperative Atrial Fibrillation: Novel and Safe Strategy Based on the Modulation of the Antioxidant System - Rodrigo, Ramón (Frontiers in Physiology, 2012)
Postoperative atrial fibrillation (AF) is the most common arrhythmia following cardiac surgery with extracorporeal circulation. The pathogenesis of postoperative AF is multifactorial. Oxidative stress, caused by the unavoidable ischemia–reperfusion event occurring in this setting, is a major contributory factor. Reactive oxygen species (ROS)-derived effects could result in lipid peroxidation, protein carbonylation, or DNA oxidation of cardiac tissue, thus leading to functional and structural myocardial remodeling. The vulnerability of myocardial tissue to the oxidative challenge is also dependent on the activity of the antioxidant system. High ROS levels, overwhelming this system, should result in deleterious cellular effects, such as the induction of necrosis, apoptosis, or autophagy. Nevertheless, tissue exposure to low to moderate ROS levels could trigger a survival response with a trend to reinforce the antioxidant defense system. Administration of n−3 polyunsaturated fatty acids (PUFA), known to involve a moderate ROS production, is consistent with a diminished vulnerability to the development of postoperative AF. Accordingly, supplementation of n−3 PUFA successfully reduced the incidence of postoperative AF after coronary bypass grafting. This response is due to an up-regulation of antioxidant enzymes, as shown in experimental models. In turn, non-enzymatic antioxidant reinforcement through vitamin C administration prior to cardiac surgery has also reduced the postoperative AF incidence. Therefore, it should be expected that a mixed therapy result in an improvement of the cardioprotective effect by modulating both components of the antioxidant system. We present novel available evidence supporting the hypothesis of an effective prevention of postoperative AF including a two-step therapeutic strategy: n−3 PUFA followed by vitamin C supplementation to patients scheduled for cardiac surgery with extracorporeal circulation. The present study should encourage the design of clinical trials aimed to test the efficacy of this strategy to offer new therapeutic opportunities to patients challenged by ischemia–reperfusion events not solely in heart, but also in other organs such as kidney or liver in transplantation surgeries.